2019
DOI: 10.1002/mnfr.201900341
|View full text |Cite
|
Sign up to set email alerts
|

The Alternaria Mycotoxin Alternariol Triggers the Immune Response of IL‐1β‐stimulated, Differentiated Caco‐2 Cells

Abstract: ScopeAlternariol (AOH), a toxic secondary metabolite of Alternaria spp., may contaminate a broad spectrum of food and feed. Besides its cytotoxic, genotoxic, and estrogenic properties, several studies report the potential of AOH to suppress the rich network of immune responses. The specific effect of AOH on inflammation‐related signaling in non‐immune cells of the intestinal epithelial layer has, however, not been investigated yet. Since intestinal epithelial cells (IECs) are, compared to underlying cells, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…An aqueous extract with a low molecular weight (< 3 kDa) fraction of the white button mushroom (Agaricus bisporus) has displayed a responsible activity to the indictors of HCV replication [88]. Alternaroil and alternariol derivatives (alternariol-9-methyl ether-3-O-sulphate and alternariol-9-methyl ether) of an endophytic fungus, Alternaria alternate, and their metabolites were explored for the inhibition of HCV NS3-NS4A protease [89][90][91][92]. Hawas et al [93] found that the most potent HCV NS3/4A protease isolated compound that was obtained from Fusarium equiseti were ω-hydroxyemodin and Griseoxanthone C. Furthermore, mellein, patulin, and H1-A were isolated from Aspergillus ochraceus, Penicillium griseofulvum, and Fusarium oxysporum, respectively.…”
Section: Hcv Ns3/4a Protease Inhibitors Isolated From Fungimentioning
confidence: 99%
“…An aqueous extract with a low molecular weight (< 3 kDa) fraction of the white button mushroom (Agaricus bisporus) has displayed a responsible activity to the indictors of HCV replication [88]. Alternaroil and alternariol derivatives (alternariol-9-methyl ether-3-O-sulphate and alternariol-9-methyl ether) of an endophytic fungus, Alternaria alternate, and their metabolites were explored for the inhibition of HCV NS3-NS4A protease [89][90][91][92]. Hawas et al [93] found that the most potent HCV NS3/4A protease isolated compound that was obtained from Fusarium equiseti were ω-hydroxyemodin and Griseoxanthone C. Furthermore, mellein, patulin, and H1-A were isolated from Aspergillus ochraceus, Penicillium griseofulvum, and Fusarium oxysporum, respectively.…”
Section: Hcv Ns3/4a Protease Inhibitors Isolated From Fungimentioning
confidence: 99%
“…However, AOH and AME are known for their genotoxic effects in vitro by acting as topoisomerase I or II poison (Jarolim et al 2017). Furthermore, recent studies indicate endocrine disruptive and immune modulatory properties (Dellafiora et al 2018;Kollarova et al 2018;Schmutz et al 2019). Several reports are available on the occurrence of mycotoxins in breast milk and were reviewed before by Warth et al (2016) and Sengling Cebin Coppa et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for the apparent discrepancy might arise from technical issues, namely the fixation of the cells in the SRB assay by trichloroacetic acid (Skehan et al 1990). Caco-2 cells have been reported to possess rigid tight junctions leading to high TEER values of above 400 Ω × cm 2 (Schmutz et al 2019). Therefore, dead cells that are still integrated in the monolayer might be measured as an artefact in total protein content.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultivated under humidified conditions (37 °C, 5% CO 2 , 95% humidity) in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% (v/v) fetal calf serum (FCS), 1% (v/v) penicillin/streptomycin (P/S; 100 U/mL/100 µg/mL), 1% (v/v) potassium pyruvate and 0.01 mg/mL transferrin. Cells were sub-cultivated twice a week at a confluency of 80%, seeded for experiments in 96-well or 24-well tissue culture plates (Cell+, Sarstedt, Nümbrecht, Germany) at a density of 85,000 cells/cm 2 and allowed to grow for 7 days prior to experiments to receive a partially differentiated, tight monolayer as previously reported by Schmutz et al (2019). The used passage numbers were below 40.…”
Section: Caco-2 (C2bbe1) Cellsmentioning
confidence: 99%